PENGARUH PEMBELAJARAN INTERAKTIF BERBASIS KONSEP TERHADAP AKTIVITAS DAN PEMAHAMAN KONSEP FISIKA SISWA - Fitriani, Fitriani; Sukroyanti, Bq Azmi; Prayogi, Saiful (IKIP Mataram, 2017)
This research aims to know the influence of interactive learning based on concept toward activity and physic concept understanding at student of SMPN 19 Mataram in academic year 2016/2017. The type of this research is experimental queasy research. The population in this research are all seventh grade student as the experimental class who are taken with purposive sampling technique. The data in this research is taken with giving pre-test and post-test to student in sample class. Data collection technique is using observation sheet and test. The result of research shows that student learning activity in experimental class is gotten the average score 80% with active category in learning process, student learning activity in control class in gotten 75% average score with active enough category in learning process. The average score of concept understanding in experimental class is 88 and control class is 75. The result hypothesis test with t-test on 5% significant level shows that t-count > t-table = (5,28 > 1,67), this means that Ha is accepted, so this can be concluded that interactive learning process based on the concept has influence toward activity and student concept understanding.